Global and regional myocardial and circulatory function during anaesthesia in the normal heart and in the presence of threatening or overt myocardial ischemia - Coetzee, Andreas Retief (Stellenbosch : Stellenbosch University, 2013)
Thesis (DSc)--Stellenbosch University, 2013.